(untitled) (Journal of the College of Education for Women, 2019)
An idiom is a group of words whose meaning put together is different from the meaning ofindividual words. English is a rich language when it comes to idioms, they represent variety. Forforeign learners, idioms are problematic because even if they know the meaning of individualwords that compose an idiom the meaning of it might be something completely different.The present study investigates Iraqi third year college students’ recognition of idioms. Toachieve this, the researchers have conducted a test which comprises three questions. Certainconclusions are reached here along with some suggestions and recommendations.